Food Delivery Monitoring System with a Line Follower Robot - Zulkifily, Muhammad Zafran; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2021)
This project offers contactless food delivery. The food delivery robot works autonomously to deliver food for patients. It comes with sensors and a line detection mechanism with turning at 30, 45 and sharp curves. Arduino Uno is used as a microcontroller to process and manage the input data, and control responses for output data. The infrared sensors are used to recognise the line. The ultrasonic sensors are used to sense obstacles and hence, stop the tray movement. The monitoring system is linked to Blynk app. The total length of track is 10 meters.The time taken for food delivery to reach every station is recorded with two different weights. It is concluded that the developed system can perform contactless food delivery and also can avoid crashing into people when someone blocks the movement of the robot.